Antibiotic Resistance in Vibrio Bacteria Associated with Red Spotting Disease in Sea Urchin Tripneustes gratilla (Echinodermata) - Mayan Ben Natan; Matan Masasa; Nadav Shashar; Lior Guttman (Microorganisms)
The red spotting disease harms sea urchins to the extent of mass mortality in the ocean and echinocultures, accompanied by environmental damage and economic losses. The current study emphasizes the antimicrobial resistance of three isolated bacteria, closely related to Vibrio harveyi, Vibrio owensii, and Vibrio fortis, associated with red spotting in the cultured sea urchin Tripneustes gratilla. In vitro trials examined the susceptibility of these bacterial isolates to various antibiotics. In addition, using an in silico examination, we revealed the arsenal of antimicrobial resistance genes in available genomes of various pathogenic Vibrio associated with diseases in sea urchins, fish, shellfish, and corals. These two approaches enabled the discussion of the similarities and differences between aquatic pathogenic Vibrio and their antibiotic resistance. Among them, we revealed a core resistance to tetracyclines and penams by the in vitro examined strains. At the same time, the in silico study also supported this core resistance by the presence of the adeF and CRP genes in the bacterial genomes. Nevertheless, variability and specific resistance were evident at the species and strain levels in the Vibrio bacteria and genomes. The in vitro trials highlighted the diverse resistance of the Vibrio harveyi-like isolate to all examined antibiotics, while the other two isolates were found susceptible to nitrofurantoin and sulfamethoxazole. The resistance of the Vibrio harveyi-like isolate could not have been obtained in the genome of the proposed relative of Vibrio harveyi VHJR7 that lacks the oqxA and oqxB genes, which enables such a resistance. A unique sensitivity of the Vibrio fortis-like isolate to erythromycin is proposed when compared to other isolated Vibrio and Vibrio genomes that seem capable of resisting this drug. According to the results, we propose nitrofurantoin or sulfamethoxazole for treating two of the red-spotting-associated isolates (Vibrio fortis and Vibrio owensii-like), but not Vibrio harveyi-like. We assume that a shared resistance to some antibiotics by Vibrios is gained by a horizontal gene transfer while previous exposures of a bacterial strain to a specific drug may induce the development of a unique resistance. Finally, we discuss the novel knowledge on antibiotic resistance in Vibrio from the current research in light of the potential risks when using drugs for disease control in aquaculture.